2019
DOI: 10.1002/slct.201802187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Ultrasonication‐Assisted Alkali Pretreatment and Enzymatic Hydrolysis on Cellwall Polysaccharides of Pennisetum Grass Varieties as Potential Biofuel Feedstock

Abstract: Production of renewable fuel like bioethanol from plant biomass and agro wastes will be the future energy source to combat the depletion of fossil fuels. The first detailed profile of the non‐cellulosic cell wall polysaccharides of native, ultrasonication assisted alkaline (NaOH) pre‐treated and enzyme hydrolysed Pennesitum grass varieties viz. hybrid Napier grass and denanath grass, were identified using glycome profiling. The best pre‐treatment conditions resulted in 89.3% and 86.7% delignification of denana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Similar trend was reported by Subhedar and Gogate [13] who observed that duty cycle till optimum increment causes increment in delignification with maximum delignification of 70.92 % elucidated at 70% duty cycle. Mohapatra et al [44] also reported that increment in duty cycle and time resulted in higher yields only till an optimum condition of 50% duty cycle and 30 min as the time with maximum yield as 135.8 mg/g for denanath grass as the substrate.…”
Section: Resultsmentioning
confidence: 98%
“…Similar trend was reported by Subhedar and Gogate [13] who observed that duty cycle till optimum increment causes increment in delignification with maximum delignification of 70.92 % elucidated at 70% duty cycle. Mohapatra et al [44] also reported that increment in duty cycle and time resulted in higher yields only till an optimum condition of 50% duty cycle and 30 min as the time with maximum yield as 135.8 mg/g for denanath grass as the substrate.…”
Section: Resultsmentioning
confidence: 98%
“…This may be due to increased effects of cavitation that enhanced the rates of reactions. 26 The sonication time required depends on the amplitude. The mutual interaction between amplitude ( X 2 ) and sonication time ( X 4 ) was found to be significant, as the model Prob > F is less than 0.05, as shown in Figure 2 e. The pretreatment time for SCB was shortened from 60 to 45 min by increasing the amplitude from 68.4 to 102.6 μm for high lovastatin production (1705–2295 μg/g).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of sonication time, as shown in Figure c,e,f, lovastatin production increased with an increase in sonication time to 60 min. This may be due to increased effects of cavitation that enhanced the rates of reactions . The sonication time required depends on the amplitude.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment of DG and HNG was conducted using ultrasonication-assisted NaOH (UA-NaOH) conditions as previously described in Mohapatra et al 28 The pretreated DG and HNG biomass were further saccharified with the most suitable parameters using two different sets of enzymes. In the first set, the combination of two commercial enzymes, that is, Palkonal MBW (a mixture of cellulase-12 000 Maps cellulase unit (MCU)/mL and hemicellulose-5000 MHCU/ mL, 28 was considered. The second set of enzymes consisted of an isolated cellulase (IC) + commercial xylanase (Xyl) (enzyme activity of the IC was 1.35 U/ mL and 8450 U/mL for Xyl enzyme).…”
Section: Pretreatment and Saccharification Of Grass Biomassmentioning
confidence: 99%